Advancing Secure Communication in the Quantum Era through the Integration of Artificial Intelligence and Quantum Cryptographic Techniques: Author's Country: India - Hemant N Chaudhari; Bayu Priyatna; Agustia Hananto (Buana Information Technology and Computer Sciences (BIT and CS), 2026)
Utilizing the ideas of quantum physics, quantum cryptography is quickly becoming a vital defense against the growing cybersecurity risks of the contemporary day, especially in light of developing quantum computing. This essay investigates the complex field of quantum cryptography and looks at how it can transform network security and protect private data. We examine the fundamental ideas of quantum cryptography, such as Quantum Key Distribution (QKD) protocols like BB84 and E91, which use quantum features like superposition and entanglement to provide potentially indestructible secure communication channels. We also discuss the urgent need for quantum-resistant solutions in view of the developing "quantum threat" to well-known cryptographic algorithms like RSA and AES. The potential benefits and difficulties of using artificial intelligence (AI) techniques to boost quantum cryptography systems' resilience and efficiency are also examined. The creation of effective quantum repeater networks and enhanced security proofs are among the outstanding research topics, future difficulties, and present implementations in quantum cryptography that are covered in this study. We stress how crucial quantum cryptography is to protecting sensitive communications in the quantum era for a variety of industries, including the military, government, financial industry, and healthcare. We come to the conclusion that quantum cryptography has enormous potential for protecting vital information systems from future cyberattacks that are becoming more complex, even if we acknowledge the technology's early stages of development.